2016
DOI: 10.1016/j.jbiotec.2016.03.022
|View full text |Cite
|
Sign up to set email alerts
|

A signature of 12 microRNAs is robustly associated with growth rate in a variety of CHO cell lines

Abstract: As Chinese Hamster Ovary (CHO) cells are the cell line of choice for the production of human-like recombinant proteins, there is interest in genetic optimization of host cell lines to overcome certain limitations in their growth rate and protein secretion. At the same time, a detailed understanding of these processes could be used to advantage by identification of marker transcripts that characterize states of performance. In this context, microRNAs (miRNAs) that exhibit a robust correlation to the growth rate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
13
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 105 publications
2
13
0
1
Order By: Relevance
“…Ectopic expression of miR-29b-1 and miR-29a decreased CHO-K1 cell proliferation, colony formation and cell invasion. These data agree with a report showing that miR-29b and miR-29a negatively correlated with CHO-K1 cell growth (Klanert et al, 2016) and corroborates miR-29's repressive functional role in cells (Garzon et al, 2009; Kwon et al, 2014; Mott et al, 2007; Xiong et al, 2010). Earlier we reported that 4-OHT increased miR-29b-1/a expression in LY2 endocrine-resistant breast cancer cells based on microarray analysis of miRNA expression (Manavalan et al, 2011) and recently confirmed this observation by qPCR (Muluhngwi et al, 2017).…”
Section: Discussionsupporting
confidence: 93%
See 4 more Smart Citations
“…Ectopic expression of miR-29b-1 and miR-29a decreased CHO-K1 cell proliferation, colony formation and cell invasion. These data agree with a report showing that miR-29b and miR-29a negatively correlated with CHO-K1 cell growth (Klanert et al, 2016) and corroborates miR-29's repressive functional role in cells (Garzon et al, 2009; Kwon et al, 2014; Mott et al, 2007; Xiong et al, 2010). Earlier we reported that 4-OHT increased miR-29b-1/a expression in LY2 endocrine-resistant breast cancer cells based on microarray analysis of miRNA expression (Manavalan et al, 2011) and recently confirmed this observation by qPCR (Muluhngwi et al, 2017).…”
Section: Discussionsupporting
confidence: 93%
“…miR-29b-1 and miR-29a were downregulated in growing CHO-K1 cells (Klanert et al, 2016). We observed 4-OHT stimulated the expression of miR-29b-1 and miR-29a in CHO-K1 cells (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations